Polyacrylamide’s Rheological and Physicochemical Properties: Analysis and Applications - Asrorov, Ummatjon A. (East European Journal of Physics, 2024)
This study presents an in-depth rheological characterization of polyacrylamide polymers produced locally, employing the Anton Paar MCR 92 (Modular Compact Rheometer). The polymer samples were systematically analyzed to understand their response to various external stimuli. Using infrared spectroscopy, the composition of the polymer was meticulously verified, ensuring a robust assessment of its molecular structure and chemical stability under different environmental conditions. Our findings elucidate the significant potential of polyacrylamide in diverse industrial applications, attributable to its adaptable viscoelastic properties and chemical resilience. The implications of this research are profound, suggesting enhanced utility of polyacrylamide in fields requiring precise material behavior modulation under dynamic conditions.